A case study of HN Healthy Meals to U - Mohd Ridwan Hakimi Ahmad (2014)
HN Healthy Meals to U, a new comer in Malaysia health food industry, the company providing healthy food delivered directly to customers located in Klang Valley, was facing difficulty in retaining sales within the market. As a start-up company, HN Healthy Meals to U had to face a number of barriers to entering the healthy food market also consumers’ behaviour toward healthy food. Top management of HN Healthy Meals to U was very concerned whether the company would be able to meet the sales target. Increasing pressure in market competition had made HN Healthy Meals to U struggle to secure profits. This had forced HN Healthy Meals to U to undergo a series of aggressive activities in response to stiff healthy food market conditions, which most of it involve promotion in marketing expenses. A market survey was conducted in 2009. Survey result revealed a significant increase in healthy food market. From the study, the root causes of sales problem encountered by HN Healthy Meals to U could be summarized into following: a) Lack of marketing development and opportunity for advancement, b) Lack of healthy lifestyle promotion, c) Uncompetitive sales system, d) Lack of recognition and appreciation of customers, and e) Dysfunctional performance marketing system. Marketing Mix program is suggested as a short-term solution for HN Healthy Meals to U. 4P’s is one of program that can targeted to solve sales problem that is due to uncompetitive marketing system, lack of promotion and appreciation of customers, as well as dysfunctional performance marketing system. As a long-term solution, the company is highly recommended to develop second strategy for the marketing development of its customers. Marketing strategy is recommended to solve sales problem due to lack of market development and opportunity for advancement, as well as lack in consumer’s awareness of healthy lifestyle. Marketing Mix is an ongoing process. Four key components: the product availability, promotion, pricing and placement must be committed to the success of this process to ensure mutual benefits for all parties.